Identification of Adenosine-3’, 5’-Cyclic Monophosphate Purufied From Leukaemic Human Urine - ., H. G. Hasan; Mohammad, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Human urinary Adenosine-3’,5’-cyclic monophosphate (cAMP) was studied in 90 normal healthy volunteers (49 males and 41 females) aged between (11 months -55 years), and 86 leukemia patients (48 males and 38 females) of four types (25 ALL, 28 AML, 14 CLL, 19 CML) aged between (11 months - 65 years). The study includes the following:- Extraction and purification of urinary cAMP from the interfering nucleotides, proteins, phosphates and pyrophosphates, by using Zinc sulphate â€“Barium hydroxide precipitation. The extracted cAMP was purified by using Dowax 50W-H+ hydrogen form column chromatography (1x5 cm). Identification of the purified cAMP, this was achieved by applying the following techniques: a- U.V analysis: - Scanning the samples and standard cAMP at (220-300 nm) in acidic, basic and neutral pH by using (Helios alpha type) spectrophotometer. Shifts in the wave length were found in acidic and basic mediums comparing with the neutral pH for all of standard, normal and leukemia cAMP. b- TLC analysis: - Using Silica gel G60 (20 X 20 cm) TLC plates with solvent system (n- butanol: glacial acetic acid: water, (2:5:3 V/V). The Rf value for standard was 0.44 cm and for purified normal and leukemia cAMP were found to be closer to the standard value (0.43 and 0.45 cm respectively). c- HPLC analysis: - Using HPLC 10AVP consist of two deliver pumps, with methanol: water 50:50 V/V as mobile phase and flow rate of 1ml/min, the separation was performed on reversed phase (250 X 4.6 mm column). The eluted chromatogram was monitored by U.V-VIS 10AVSPD detector The retention time of urinary cAMP obtained from normal healthy and leukemic patients was 3.02 min which was close enough to the standard retention time. The results of the study showed that the level of purified normal and leukemia cAMP are of the values 15.87 Â± 2.4 Î¼mole/24 hours and 20.13 Â± 0.881 Î¼mole/24 hours respectively.